Effects of lactation number and different stage of lactation on milk yield of Indigenous and Crossbred cows in Bangladesh - Ahmad, S; Hossain, FMA; Islam, N (International Journal of Natural Sciences, 2011)
A total of 54 samples were collected from 18 milking cows from which nine were indigenous and nine were crossbred to evaluate the effects of different lactation number and different stage of lactation on the milk yield. The average daily milk yield of indigenous and crossbred cows at 1st, 2nd and 3rd lactation were 1.311, 1.633, 2.072 and 8.917, 9.567, 10.167 liter/day/cow respectively and represented the significant difference (p<0.01) within the daily milk yield of different lactations. Milk yield increased gradually from 1st to 3rd lactation. The highest milk yield was recorded in 3rd lactation and lowest was in 1st. The mean milk yield of indigenous and crossbred cows at early, middle & later stages of lactations were 1.617, 2.094, 1.306 and 9.389, 10.222, 9.039 liter/cow/day respectively that revealed stages of lactation had significant effect (p<0.01) on milk yield per day. It was observed that milk yield decreased after 2nd stage of lactation and decreased linearly up to the end of lactation. The highest milk yield was recorded in 2nd stage of lactation and lowest was in 3rd stage of lactation. The overall milk production in different lactation for indigenous cows was 1.672 liter/day and for crossbred cows was 9.550 liter/day that may be concluded as crossbred cows are superior to indigenous in concern of milk yield. Keywords: Indigenous cows; crossbred cows; lactation number; stage of lactation; milk yield. DOI: http://dx.doi.org/10.3329/ijns.v1i1.8614 International Journal of Natural Sciences (2011), 1(1):31-34